DOCTRINAL RESEARCH AS A MEANS TO RECOVER NORMATIVE THINKING IN ACCOUNTING - Daniel COETSEE; Pieter BUYS (Studia Universitatis Babeș-Bolyai. Philosophia)
Doctrinal Research as a Means to Recover Normative Thinking in Accounting. The article debates whether legal doctrinal research could be applied in contemporary accounting research to bring back the prescriptive nature of normative research and whether, by applying doctrinal research, a new focus could be created in accounting research. The article found that the main difference between doctrinal research and traditional scientific and social research is that the focus of doctrinal research is not on the development of theories, but on the underlying doctrines, concepts, rules and principles on which practice and the practical system are based. A shift in accounting research from traditional research that creates theory to research that focuses on the underlying doctrines of the accounting discipline would create an insider perspective in accounting research, which could bring accounting research closer to accounting practice. Doctrinal research could bring normative and prescriptive aspects back to accounting research, but such normative aspects will not necessarily be similar to traditional normative research.